Poland : studies on the social dimensions of globalization - Torres, R....[et al] (ILO GenevaCH, 2001)
Describes how the process of economic globalization has proceeded in Poland. Analyzes the impact of globalization on the economic and social development of the country. Explores the policy options that may help improve the gains from globalization, while at the same time reducing its costs.